Ukraineʼs security and global stability: strategies and ways of ensuring in conditions of war - Havryliuk, Ivan; Semenenko, Oleh; Vodchyts, Oleksandr; Dobrovolskyi, Yuzef; Mytchenko, Serhii; Korotia, Volodymyr (Social Development and Security, 2024)
Purpose: determining the main strategies for ensuring Ukraine’s victory in the Russian-Ukrainian war and ways to ensure its security through global stability. Method: methods of analysis and synthesis, deduction and induction, method of analogies and comparison. Practical implications: the main strategies for ensuring Ukraine’s victory in the Russian-Ukrainian war are determined; the ways of practical implementation of these strategies have been formed, and the list of measures necessary for the implementation of these ways has been revealed; general conclusions were formed regarding the implementation of each of the strategies in the global system of ensuring Ukraine’s victory in the war and global world stability and security. Value: the article analyzes the main strategies and ways of realizing Ukraine’s victory in the war and reveals the modern features of its support. Future research: areas of further research may be the development and improvement of cyber security strategies; information security and countering disinformation; reforming the defense sector and modernizing the armed forces; cooperation with international security organizations; energy security and diversification of energy supply; economic stability as a factor of national security; the influence of international politics on the security of Ukraine; psychological stability and readiness of the population for crisis situations; innovations in defense technologies; analysis of the impact of global climate change on national and regional security. Paper type: theoretical, practical.